Factorization Method in Oscillator with the Aharonov-Casher System - J. Sadeghi; Jalil Naji; Behnam Pourhassan (Advances in Mathematical Physics)
We review the oscillator with Aharonov-Casher system and study some mathematical foundation about factorization method. The factorization method helps us to obtain the energy spectrum and general wave function for the corresponding system in some spin condition. The factorization method leads us to obtain the raising and lowering operators for the Aharonov-Casher system. The corresponding operators give us the generators of the algebra.